Severity of sleep apnea impairs adipose tissue insulin sensitivity in individuals with obesity and newly diagnosed obstructive sleep apnea - Rodrigues, Sara; Bortolotto, Luiz Aparecido; Beyl, Robbie A.; Singh, Prachi (Frontiers in Sleep, 2023)
Obstructive sleep apnea (OSA) is a common sleep disorder associated with increased risk for the development of type 2 diabetes. While studies have examined the effects of sleep on whole body insulin sensitivity, little is known about the effects of sleep on adipose tissue insulin sensitivity in patients with OSA. We analyzed if the severity of OSA, measured by apnea-hypopnea index (AHI), is associated with adipose tissue insulin-sensitivity.We examined the relationship between sleep parameters and adipose tissue insulin sensitivity in non-diabetic participants with obesity and newly diagnosed OSA who underwent overnight polysomnography and a 2h oral glucose tolerance test during which circulating free-fatty acid were measured. Sixteen non-diabetic participants with obesity and newly diagnosed OSA (sex, 81.3% males; mean age, 50.9 ± 6.7y; BMI, 36.5 ± 2.9 kg/m 2 ; AHI, 43 ± 20 events/h) were included in the analysis.In our study participants, AHI is inversely associated with free-fatty acid suppression during oral glucose challenge (R= -0.764, p=0.001). This relationship persisted even after statistical adjustment for age (R= -0.769, p=0.001), body mass index (R= -0.733, p=0.002), waist to hip ratio (R= -0.741, p=0.004), or percent body fat mass (R= -0.0529, p=0.041). Furthermore, whole body insulin sensitivity as determined by Matsuda index was associated with percent REM sleep (R= 0.552, p=0.027) but not AHI (R= -0.119, p=0.660).In non-diabetic patients with OSA, severity of sleep apnea is associated with adipose tissue insulin sensitivity but not whole-body insulin sensitivity. The impairments in adipose tissue insulin sensitivity may contribute to development of type 2 diabetes.